2000
DOI: 10.1091/mbc.11.5.1859
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Nitric Oxide in Muscle Repair: Nitric Oxide–mediated Activation of Muscle Satellite Cells

Abstract: Muscle satellite cells are quiescent precursors interposed between myofibers and a sheath of external lamina. Although their activation and recruitment to cycle enable muscle repair and adaptation, the activation signal is not known. Evidence is presented that nitric oxide (NO) mediates satellite cell activation, including morphological hypertrophy and decreased adhesion in the fiber-lamina complex. Activation in vivo occurred within 1 min after injury. Cell isolation and histology showed that pharmacological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
371
0
12

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 383 publications
(394 citation statements)
references
References 120 publications
11
371
0
12
Order By: Relevance
“…In myotube cultures, cyclical stretch for 2 d was reported to increase NO production and nNOS concentration in a calcium-dependent manner (Tidball et al, 1998), and the same study showed that resumption of weight bearing after muscle unloading restored normal nNOS expression and NO release, as did electric stimulation and passive stretch of excised muscle. It is interesting in this regard that in dystrophic muscle without dystrophin, nNOS was absent from the subsarcolemmal region (Brenman et al, 1995(Brenman et al, , 1996 and that dysregulation of satellite cell activation in vivo was reportedly very similar to that occurring as a result of absent nNOS expression or NOS inhibition (Anderson, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In myotube cultures, cyclical stretch for 2 d was reported to increase NO production and nNOS concentration in a calcium-dependent manner (Tidball et al, 1998), and the same study showed that resumption of weight bearing after muscle unloading restored normal nNOS expression and NO release, as did electric stimulation and passive stretch of excised muscle. It is interesting in this regard that in dystrophic muscle without dystrophin, nNOS was absent from the subsarcolemmal region (Brenman et al, 1995(Brenman et al, , 1996 and that dysregulation of satellite cell activation in vivo was reportedly very similar to that occurring as a result of absent nNOS expression or NOS inhibition (Anderson, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Anderson (2000) demonstrated that NO mediated the rapid morphological changes associated with satellite cell activation after crush injury, including cell hypertrophy and detachment from the adjacent fiber. At the cellular level, shear forces generated by contraction or re-traction of damaged fibers within the basal lamina are thought to stimulate nitric-oxide synthase (NOS) to produce bursts of NO synthesis.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…via nitrogen dilution hypoxic generators) does not [131]. Nitric oxide is a potent reactive species and has been proposed to mediate the activation of skeletal muscle satellite cells and subsequent hypertrophy [132]. It is therefore possible that the type of hypoxia employed during IHRT may influence the subsequent physiological responses.…”
Section: Intramuscular Signalling Pathwaysmentioning
confidence: 99%